On-line analysis of volatile chlorinated hydrocarbons in air by gas chromatography-mass spectrometry Improvements in preconcentration and injection steps - ZOCCOLILLO, Lelio; INSOGNA, SUSANNA; L. Amendola; E. Pastorini (Journal of Chromatography A, 2010)
An analytical system composed of a cryofocusing trap injector device coupled to a gas chromatograph with mass spectrometric detection (CTI-GC-MS) specific for the on-line analysis in air of volatile chlorinated hydrocarbons (VCHCs) (dichloromethane; chloroform; 1,1,1-trichloroethane; tetrachloromethane; 1,1,2-trichloroethylene; tetrachloroethylene) was developed. The cryofocusing trap injector was the result of appropriate low cost modifications to an original purge-and-trap device to make it suitable for direct air analysis even in the case of only slightly contaminated air samples, such as those from remote zones. The CTI device can rapidly and easily be rearranged into the purge-and-trap allowing water and air analysis with the same apparatus. Air samples, collected in stainless steel canisters, were introduced directly into the CTI-GC-MS system to realize cryo-concentration (at -120 degrees C), thermal desorption (at 200 degrees C) and for the subsequent analysis of volatiles. The operating phases and conditions were customised and optimized. Recovery efficiency was optimized in terms of moisture removal, cold trap temperature and sampling mass flow. The injection of entrapped volatiles was realized through a direct transfer with high chromatographic reliability (capillary column-capillary column). These improvements allowed obtaining limits of detection (LODs) at least one order of magnitude lower than current LODs for the investigated substances. The method was successfully employed on real samples: air from urban and rural areas and air from remote zones such as Antarctica. (C) 2010 Elsevier B.V. All rights reserved.